Birds eye view San Luis Obispo Cal. - Cal Polytechnic School in distance - Frank Aston::::::photographer:::
Birds-eye view -- San Luis Obispo Cal. -- Cal. Polytechnic School in Distance'; looking north across San Luis; Cerro San Luis and Bishop's Peak in left background